Review of Literature on Factors Influencing Public Sector Disclosure: The Way Forward - Abu Bakar, Nur Barizah; Saleh, Zakiah (Asian Journal of Business and Accounting, 2015)
This study aims to review the development of research undertaken in understanding the factors influencing public sector disclosure and to suggest future research in this area. This study focuses on academic online databases by conducting keyword searches which are supplemented by backward and forward searching techniques. Relevant articles found are then reviewed and discussed based on four phases of their publication period: prior to 1990, from 1990 to 1999, from 2000 to 2009, and from 2010 and after. Three important observations are made. First, studies on US dominated research in this area but in recent years, more European and other developed countries are being included. Second, a vast majority of these studies tend to focus on local authorities. Third, the financial aspect of disclosure appears to be receiving the greatest attention but it is noted that researchers are starting to show a greater interest in reporting the concept of sustainability. From these observations, it is suggested that more studies be conducted on developing countries and other types of governments besides those carried out on local governments. Apart from focusing on financial disclosures, it is also recommended that future research should look at other aspects such as accountability disclosure. Keywords: Disclosure, Factors, Literature Review, Motivations, Public Sector, Reporting JEL Classification: M41, M48, H83